Welding of the steel grade S890QL - Celin, Roman (Materiali in tehnologije, 2014)
Quenched and tempered high-strength steels are widely used in the construction of steel structures. However, because of their properties, care must be taken in order to determine suitable welding parameters. One way is to use the weld-heat-flow theory with the use of the weld-bead cooling time t8/5 and the recommendations of the standard EN 1011-2. The chosen weld parent material was high-strength S890QL steel with the filler welding wire G Mn4Ni1.5CrMo, which were used to produce a sound butt weld. Mechanical testing and a metallographic examination of the weld samples were carried out. The tensile test showed undermatching of the weld joint, with a satisfactory Charpy V notch toughness. The metallographic investigation revealed a microstructure variation in different areas of the weld joint. The highest values of the hardness HV10 were measured in the heat-affected zone.
Keywords: varjenje; welding; visokotrdno jeklo; high-strength steel; cooling time t8/5; čas ohlajanja; microstructure; mikrostruktura; mechanical testing; mehanske preiskave